Developing Leadership Skills Among Librarians In Organizations - Haji Muhamad, Mastura (2015)
Being a leader can be a very humbling experience. Taking the helm of an already well-established public library and developing leadership skills among librarians while one's self is not a librarian is a great challenge. The rebranding of Selangor Public Library is an opportunity to meet that challenge head-on, and its processes, the subject of this paper.